Busana Kontemporer dengan Batik Motif Nebula Orion - Fatricia M; Mega Kencana; Desra Imelda; Fadri Rahmat (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The creation of this artwork is inspired by the cosmic visual beauty of the Orion Nebula (Messier 42), an astronomical phenomenon featuring a giant molecular cloud that emits dramatic color gradations from hydrogen gas and cosmic dust. These abstract, dynamic, and irregular visual characteristics are transformed into the realm of fashion through the design of contemporary clothing combined with modern batik. The creation methods applied include exploration (observation, literature study), material experimentation, design processes (trends, moodboard, sketches), and the physical realization of the garments. This contemporary clothing collection is classified into three fashion tiers utilizing core materials such as cotton dobby fabric (as the medium for manual batik), black velvet (representing outer space), silk foil, and ombre silk chiffon and pleated tulle. The three categories consist of: Ready-to-Wear (titled Abendstern) which focuses on functional-minimalist male silhouettes; Ready-to-Wear Deluxe (titled Staubwelle) featuring more complex asymmetrical construction, luxurious textures, and a glow-in-the-dark effect; and Haute Couture (titled Himmelskonigin) as the pinnacle of women's high fashion, exploring layered draping techniques and dramatic scattered sequin details. Through the deconstruction of Indonesian heritage textiles (wastra nusantara), this work successfully harmonizes transcendent cosmic imagination with a modern, international fashion outlook, presented through a fashion show at the Hoeridjah Adam Building, ISI Padangpanjang.